2017
DOI: 10.1186/s12880-017-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

MRI texture analysis in differentiating luminal A and luminal B breast cancer molecular subtypes - a feasibility study

Abstract: BackgroundThe aim of this study was to use texture analysis (TA) of breast magnetic resonance (MR) images to assist in differentiating estrogen receptor (ER) positive breast cancer molecular subtypes.MethodsTwenty-seven patients with histopathologically proven invasive ductal breast cancer were selected in preliminary study. Tumors were classified into molecular subtypes: luminal A (ER-positive and/or progesterone receptor (PR)-positive, human epidermal growth factor receptor type 2 (HER2) -negative, prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 45 publications
2
58
1
Order By: Relevance
“…Relatively, analysis based on one single slice would inevitably lose a lot of important information because of heterogeneity in tumor volume. Hence, some previous studies conducted the 3D segmentation for radiomic analysis (11,(54)(55)(56). It must be pointed out that in order to achieve 3D segmentation, the image data should be acquired using the isotropic acquisition when the cases were initially scanned.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively, analysis based on one single slice would inevitably lose a lot of important information because of heterogeneity in tumor volume. Hence, some previous studies conducted the 3D segmentation for radiomic analysis (11,(54)(55)(56). It must be pointed out that in order to achieve 3D segmentation, the image data should be acquired using the isotropic acquisition when the cases were initially scanned.…”
Section: Discussionmentioning
confidence: 99%
“…In each loop of the LOOCV, one sample was retained as the test case, and the other samples were used as the training set. At each LOOCV loop, feature selection procedure based on least absolute shrinkage and selection operator (LASSO) was applied on the training set 33,45‐49 . The procedure was repeated for all the LOOCV folds, and a classification score was generated for each test case.…”
Section: Methodsmentioning
confidence: 99%
“…14 Therefore, an accurate evaluation of Ki-67 status is important for the prognostic analysis of breast cancer; however, the accuracy of traditional invasive detection methods, namely biopsies, is influenced by sampling errors as biopsies may often not be sufficient in assessing intratumoural heterogeneity expression. 15,16 Breast magnetic resonance imaging (MRI) has a high sensitivity in the detection of breast cancer 17,18 and has played an important role in the detection, diagnosis, and staging of breast cancer. Previous studies have shown that variable MRI findings, such as apparent diffusion coefficient (ADC) values 19 and entropy-based features analysed by texture analysis, 16 correlate with Ki-67 status.…”
Section: Introductionmentioning
confidence: 99%